Electron transport study on functionalized armchair graphene nanoribbons: DFT calculations. Issue 26 (23rd February 2016) - Gracia-Espino, E.; López-Urías, F.; Terrones, H.; Terrones, M.
Abstract : Quantum transport studies are performed on doped (boron, nitrogen, oxygen, silicon, phosphorus, and sulfur) and functionalized (borane, amine, hydroxyl, thiol, silane, silene, phosphine, and phosphorane) armchair graphene nanoribbons by means of density functional theory. Abstract : Quantum transport studies are performed on doped and functionalized 8- and 11-armchair graphene nanoribbons (aGNRs) by means of density functional theory. Substitutional doping is performed by introducing boron, nitrogen, oxygen, silicon, phosphorus, and sulfur atoms within the lattice of the aGNRs. Other functional groups such as borane, amine, hydroxyl, thiol, silane, silene, phosphine, and phosphorane groups are also introduced at the nanoribbon's edge. The dopant position and the nanoribbon's width strongly influence the current–voltage characteristics, and generally, the narrow 8-aGNRs and edge-doped 11-aGNRs show deteriorated transport properties, mainly due to the formation of irregular edges that create highly localized states disrupting several conducting bands. On the other hand, the inside-doped 11-aGNRs are barely affected, mainly because these systems preserve the edge's structure, thus edge conduction bands still contribute to the electron transport. Our results suggest that wider graphene nanoribbons could be functionalized at the inner sections without significantly compromising their transport characteristics while retaining the chemical reactivity that characterize doped nanocarbons. Such characteristics are highly desirable in fuel cells where doped graphene is used as a catalyst support or as a metal-free catalyst.